A prospective study evaluating the impact of implementing 'bundled interventions' in reducing surgical site infections among patients undergoing surgery for gynaecological Malignancies. (December 2019) - Agarwal, Reshu; Y Sannappavar, Nataraj; Appukuttan, Akhila; Ashok, Anjitha; Rajanbabu, Anupama
Abstract: Objective: To investigate the incidence of 30-day surgical site infection (SSI) rate before and after the introduction of evidence-based "bundled interventions" (BI) in gynaecological malignancy (GM).To evaluate the efficacy of BI in reducing SSI rate and readmission rate due to SSI. Methods: This prospective interventional study was carried out at a Single University teaching hospital. BIs were implemented in GM laparotomies from March 2016 to June 2018. Baseline SSI rate was determined retrospectively from January 2011 to December 2015. The interventions included patient education, separate closing tray, dressing removal ≤48 h, dismissal with 4% chlorhexidine gluconate and follow up phone call. A 30-day SSI and re-admission rate were assessed. Results: The study included 840 patients, 624 who underwent laparotomy before (PRE) the implementation of BI and 216 after (POST) the implementation. The most common diagnosis was ovarian cancer (OC). There was significant reduction in: overall (p < 0.001) and superficial SSI rates (p < 0.001); OC undergoing surgery without bowel resection (BR) (p < 0.001); and OC with BR (p = 0.003), after implementation of BI. None of the patients had deep organ/space infections or readmissions during the Post-intervention period. The overall compliance for BI was 96.7%. SSI rates significantly decreased in patients aged ≥ 60 years, ASA score ≥ 3, operative time ≥ 240 min, clean contaminated and contaminated surgeries, and prolonged hospital stay (all p < 0.05). Conclusion: Implementation of BI was associated with significant reduction of SSI rate in GM. The intervention remained effective in at-risk patients with non-modifiable clinico-pathologic and surgical factors.